On the emerging challenges in the services industry: Trade and investment - Florian A. Alburo (University of the Philippines, School of Economics (UPSE), 2018)
The paper examines recent technology enablers as these affect the services sector and are seen to be analogous to developments taking place as Industry 4.0. After briefly summarizing these, we argue that there are important implications to services, particularly their international trade, in terms of challenges to investment, regulation, policy, regional cooperation, and regional agreements, among others. Some of the possible adjustments arising out of these developments are outlined - in the manufacturing sector and in the services (and their trade).
Keywords: 330; trade and investment